COBIT 5: How Capable PT GTI Governing Innovation, Human Resource, and Knowledge Aspect? - Darwin Aridarno Sudarnoto; Wella Wella; Ririn Ikana Desanti (ULTIMA InfoSys, 2021)
The performance of information technology governance by PT GTI has not been optimal and there has never been a measurement of information technology governance capability. Based on these problems, it is necessary to measure the capability of information technology governance and make an appropriate information technology management recommendation that can be used as a guide—the measurement of the COBIT 5.0 framework. The data collection method consisted of observation, questionnaires, and interviews. The data collection results will produce findings, impacts, and recommendations for PT GTI. Measuring the capability of information technology governance used includes Planning, Preparation, Implementation, and Measurement Reporting. The study focused on 3 IT processes and obtained the following capability level results: APO04 Manage Innovation got a score of 78.4% and stopped at level 3, APO07 Managed Human Resource with a score of 81.07% and stopped at level 1, and BAI08 Manage Knowledge got to score 61% and stop at level 2.